Fluência e compreensão da leitura em escolares do 3º ao 5º ano do ensino fundamental - Martins, Maíra Anelli [UNESP]; Capellini, Simone Aparecida [UNESP] (Programa de Pós-Graduação em Psicologia, Pontifícia Universidade Católica de Campinas, 2014)
The study aims to characterize and report on performance in reading fluency and comprehension. The study sample included 97 students from 3 rd to 5 th grade at a state school in the city of Marília in São Paulo State of Brazil. The procedures involved an evaluation of reading time, prosody and text comprehension. The oral reading of a text was recorded, and a multiple choice test was applied to evaluate performance in comprehension. The results were statistically analyzed and showed that performance in students' reading fluency was able to highlight aspects of the difficulties that arise during the processing of reading.

Este estudo tem como objetivo caracterizar e relacionar a fluência na leitura e a compreensão do texto lido. Participaram da pesquisa 97 escolares do 3º ao 5º ano da rede pública de ensino do município de Marília, São Paulo. Como procedimentos, foram avaliados o tempo de leitura, a prosódia e a compreensão leitora. Foi gravada a leitura oral de um texto e aplicado um teste com questões de múltipla escolha para avaliar a compreensão. Os resultados foram analisados estatisticamente e revelaram que o desempenho em fluência de leitura dos escolares influencia aspectos das dificuldades apresentadas durante o processo.
Fluency and reading comprehension in students from 3rd to 5th of elementary school grades
Keywords: Compreensão da leitura; Educação; Leitura; Reading comprehension; Education; Reading